A meta-analysis of the effects of high-intensity interval training on circulatory system-related indicators in sedentary populations - Li, Guoshuai; Dong, Depeng (Frontiers in Physiology, 2025)
ObjectiveThis study systematically evaluated the effects of high-intensity interval training (HIIT) on circulatory indicators in sedentary populations. Following the framework of systematic review and meta-analysis, it synthesized current evidence to support the evidence-based application of HIIT in exercise interventions for sedentary individuals.MethodsThis systematic review and meta-analysis followed PRISMA guidelines and was registered on PROSPERO. We searched PubMed, Web of Science, Embase, and CNKI for studies published between January 2000 and July 2025. Inclusion criteria used the PICOS framework: Participants (sedentary individuals), Intervention (HIIT), Comparison (control), Outcomes (blood pressure, pulse wave velocity, flow-mediated dilation, heart rate), and Study type randomized controlled trials. The search yielded 434 records. After duplicate removal and screening, 14 RCTs (500 participants) were included. The Cochrane Risk of Bias tool assessed study quality, and analyses used RevMan 5.4.ResultsSignificant differences were observed between the HIIT and control groups in several outcomes: systolic blood pressure (SBP) (MD = −5.02, 95% CI: −7.29 to −2.76, P < 0.0001), diastolic blood pressure (DBP) (MD = −2.43, 95% CI: −4.08 to −0.79, P = 0.004), pulse wave velocity (PWV) (MD = −0.28, 95% CI: −0.56 to −0.01, P = 0.04), flow-mediated dilation (FMD) (SMD = 1.12, 95% CI: 0.32–1.92, P = 0.006), and heart rate (MD = −0.36, 95% CI: −0.69 to −0.03, P = 0.03). Subgroup analysis of FMD revealed no heterogeneity in studies with a mean participant age of >30 years (P = 0.38, I2 = 0%). However, substantial heterogeneity remained in studies with a mean age ≤30 years (P = 0.0003, I2 = 79%), suggesting age may be a major source of heterogeneity.ConclusionHIIT effectively improves key circulatory indicators in sedentary populations, including blood pressure, vascular elasticity, and endothelial function, making it a valuable exercise strategy for vascular health management. However, further high-quality and standardized clinical trials are needed to confirm its long-term efficacy and safety.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?, identifier CRD420251106079.